Revisiting Franco Moretti’s Concept and Practice of Literary Geography - Chen, Shuping (Bina Nusantara University, 2024)
The research observed Franco Moretti, an influential Italian literary critic who had made significant contributions to the field of literary geography, a cross-disciplinary theory that utilized geographical methods to analyze and understand literary and cultural materials. Moretti’s approach to literary geography diverged from traditional and orthodox methods, offering a fresh perspective. The research applied a qualitative method with a closereading approach to evaluate and explore Moretti’s conceptualization and implementation of literary geography through a systematic three-step research process. The first step involved identifying the intellectual and theoretical sources of inspiration that have influenced Moretti’s work. The second step focused on illuminating Moretti’s innovative understanding and interpretation of literary geography as well as his integration of literary maps into the analysis of literature. Lastly, the research investigated two case studies to further exemplify Moretti’s practices in the field of literary geography. The first case study regarded Jane Austen’s fiction, where Moretti’s approach unveils Austen’s geographical imagination of Britain in her novels. The second one centers on Mary Mitford’s ‘Our Village’, where Moretti discovered the circular narrative pattern. By undertaking these three comprehensive steps, the research offers valuable insights into literary geography’s conceptual and methodological dimensions. Additionally, it endeavors to cultivate a deeper appreciation for the interdisciplinary nature of literary geography, thereby inspiring scholars and researchers to delve further into the intersections between geography, literature, and culture.